Voices of Innovation - Payers Opportunities for Creating Solutions to Improve Member Experience and Health. - Marx, Edward W.; Dhingra, Sakshika (Oxford : Productivity Press, 2024)
This book is loaded with numerous case studies and interviews with healthcare leaders from the payer community, helping stakeholders understand how to leverage innovation leading them to superior business and clinical outcomes.
Description based upon print version of record.
Keywords: Medical care; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Management